PENGARUH KUALITAS PELAYANAN, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SHOPEE – FOOD (STUDI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UMG 2018 - 2019) - Asa Prasetya Indraswara; Moh. Agung Surianto (CV. ALIM'SPUBLISHING, 2023)
Nowadays, the number of internet users in Indonesia continues to experience a significant increase. According to data, the number of internet users in Indonesia in March 2021 reached 212.35 million, which put Indonesia in third place, with the most internet users in Asia. Internet technology is also used as an e-commerce trade transaction. A survey conducted by Katadata shows that 77.4% of internet users in Indonesia access food delivery applications. This figure is the highest presentation in the world in 2021. One of the food delivery e-commerce sites that is often used by University of Muhammadiyah Gresik students is Shopeefood. There are several factors that can cause someone to decide to buy online in e-commerce, including the Covid-19 pandemic, digital marketing promotions, sales promotions, affordable prices and also the quality of service provided. This study aims to determine the effect of service quality, price, and promotion on purchasing decisions at Shopeefood. The population of this study were students of the Faculty of Economics and Business, Muhammadiyah University of Gresik. Samples were taken of 100 students who had made a purchase transaction at Shopeefood. Data was taken using a questionnaire whose measurement used a Likert scale. The data obtained were processed and analyzed using multiple linear regression analysis techniques. The results showed that service quality and price had a significant effect, while promotions had no effect on purchasing decisions